2020
DOI: 10.1182/blood.2019002561
|View full text |Cite
|
Sign up to set email alerts
|

Novel drivers and modifiers of MPL-dependent oncogenic transformation identified by deep mutational scanning

Abstract: The single transmembrane domain (TMD) of the human thrombopoietin receptor (TpoR/myeloproliferative leukemia [MPL] protein), encoded by exon 10 of the MPL gene, is a hotspot for somatic mutations associated with myeloproliferative neoplasms (MPNs). Approximately 6% and 14% of JAK2 V617F− essential thrombocythemia and primary myelofibrosis patients, respectively, have “canonical” MPL exon 10 driver mutations W515L/K/R/A or S505N, which generate constitutively active receptors and consequent loss of Tpo dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…L498W, V501A, V501S, and L502S [394]. These oncogenic substitutions are dependent on the position and amino acid residues that are mutated [394]. Consistent with these results, the V501A mutation was found in MPN patients and recently reported to confer constitutive receptor activation [403].…”
Section: Peptide V May Be Specifically Inhibiting Tpor-mediated Cell supporting
confidence: 83%
See 3 more Smart Citations
“…L498W, V501A, V501S, and L502S [394]. These oncogenic substitutions are dependent on the position and amino acid residues that are mutated [394]. Consistent with these results, the V501A mutation was found in MPN patients and recently reported to confer constitutive receptor activation [403].…”
Section: Peptide V May Be Specifically Inhibiting Tpor-mediated Cell supporting
confidence: 83%
“…and S505N have shown that the latter conferred stronger or similar cytokine-independent proliferative activity as the W515K mutant [227,394]. In the current study, the addition of puromycin did not continue after selection.…”
Section: Peptide V May Be Specifically Inhibiting Tpor-mediated Cell supporting
(Expert classified)
See 2 more Smart Citations
“…The remaining 2% of PV patients carry somatic driver mutations in JAK2 exon 12 [ 43 , 44 ]. Another driver mutation, the thrombopoietin receptor gene MPL , is found in up to 5 or 10% of ET or PMF patients, respectively, with MPLW515L/K being the most common mutation [ 14 , 15 , 18 , 45 , 46 , 47 ]. As the JAK2V617F mutation, the MPL mutation confers constitutive, cytokine-independent activation of the JAK-STAT pathway [ 14 ].…”
Section: Genomics In Mpnsmentioning
confidence: 99%